Statistics and indicators for financial stability analysis and policy - Jean-Marc Israël; Patrick Sandars; Aurel Schubert; Björn Fischer (European Central Bank (ECB), 2013)
Timely and accurate data are key to the preparation of macro-prudential policy recommendations and decisions by the ESRB, as well as to monitoring policy decisions in terms of their impact on, or transmission to, the financial and non-financial economy. This paper illustrates the work that has been carried out by the European Central Bank, the European Systemic Risk Board and the European Supervisory Authorities over a period of more than two years from 2010 to 2012 to prepare, develop, implement and manage the initial set of statistical and supervisory information necessary to support the European Systemic Risk Board, from its inception in January 2011. The paper also touches on the statistical information that is provided to support the financial stability function of the European Central Bank.
Keywords: F31; F47; F30; 330; financial stability statistics; financial statistics; systemic risk